Heart failure biomarkers in revascularized patients with stable coronary heart disease as clinical outcome predictors - Bošnjak, Ivica; Bedeković, Dražen; Selthofer-Relatić, Kristina; Roguljić, Hrvoje; Mihaljević, Ivica; Dukić, Darko; Bilić-Ćurčić, Ines (Frontiers in Cardiovascular Medicine, 2024)
Introduction The aim of this study was to investigate serum levels of galectin-3 (Gal-3) and N-terminal pro-brain Natriuretic Peptide (NT-proBNP) in patients with stable obstructive coronary artery disease, as well as their potential to predict clinical outcomes. Methods This was a single-center cross-sectional cohort study. 168 patients were divided into three groups: percutaneous coronary intervention (PCI) group (N 64), coronary artery bypass graft surgery (CABG) group (N 57), and group with no coronary stenosis (N 47). Gal-3 and NT-proBNP levels were measured and the Syntax score (Ss) was calculated. Results The mean value of Gal-3 was 19.98 ng/ml and 9.51 ng/ml (p < 0.001) in the study group and control group, respectively. Highest value of Gal-3 was found in the group of subjects with three-vessel disease (p < 0.001). The mean value of NT-proBNP in the study group was 401.3 pg/ml, and in the control group 100.3 pg/ml (p = 0.159). The highest value of NT-proBNP was found in the group of subjects with three-vessel disease (p = 0.021). There was a statistically significant association between Gal-3, NT-proBNP and occurrence of adverse cardiovascular event (p = 0.0018; p = 0.0019). Conclusion Gal-3 and NT-proBNP could be used as an additional tool for diagnosis and severity assessment of stable obstructive coronary artery disease. Furthermore, it could help identify high-risk patients who could experience major adverse cardiovascular events.